Factors affecting to select Islamic credit cards in Pakistan: the TRA model - Muhammad, Ali; Syed Ali, Raza; Puah, Chin Hong (Emerald Group Publishing Limited, 2017)
Purpose – This paper aims to investigate the factors affecting intentions to select Islamic credit cards in Pakistan by using the theory of reasoned action (TRA) model. In general, bank customers are aware of credit card facility, but the leading factors to select Islamic credit cards are particularly unexplored. Due to this fact, the study examined the effect of subjective norm (SN) and attitude (ATT) with the inclusion of new construct, namely, perceived financial cost (PFC) to predict the intention of customers about the Islamic credit card in Pakistan. Design/methodology/approach – Sample data were conveniently drawn from the bank customers with the help of a self-administered survey based questionnaire, which was consisted over five-point Likert scale. The study uses a sample of 492 bank customers located in the biggest city of Pakistan. Out of these responses, only 466 responses were used in the analysis, while the remaining responses were ignored due to missing data and incomplete responses. The data were analyzed through factor and regression analysis. Findings – Findings from regression analysis suggest that SN and ATT show positive and significant impact on intentions to select an Islamic credit card, while PFC has a negative impact on intentions to select Islamic credit cards. Moreover, SN was found to be the most influential factor to predict the selection of Islamic credit card. Research implications – This study has some practical implications for the academicians and Islamic bank managers. Through this research, bank managers can educate their customers about Islamic credit and financial products. Not only this, they should develop a strategy for the awareness of Islamic banking products through social networking and other marketing modes. On the other side, this study laid a foundation for future researchers to explore additional predictors of Islamic credit card. Their empirical work will provide a help to benefit and understand customers’ financial knowledge. Originality/value – Islamic credit facility is entirely new in Pakistan and lacking with empirical support. Therefore, this investigation contributes to the existing body of knowledge by providing a comprehensive explanation on the Islamic credit card service in Pakistan.